2022
DOI: 10.1016/j.ultsonch.2021.105893
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of wetting on cavitation during the spreading of a filler droplet on the ultrasonically agitated Al substrate

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Yu et al [3] , [14] studied the action mechanism of ultrasonic power and liquid medium surface tension on the shape variations of cavitation bubbles near the wall by simultaneous high-speed microscopic imaging method. Xu et al [5] , [15] observed the cavitation behavior at the interface of a pure Sn thin liquid layer. They found the cavitation effect could improve the wettability of the substrate metal surface, and the cavitation effect strengthened with decreasing gap layer.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [3] , [14] studied the action mechanism of ultrasonic power and liquid medium surface tension on the shape variations of cavitation bubbles near the wall by simultaneous high-speed microscopic imaging method. Xu et al [5] , [15] observed the cavitation behavior at the interface of a pure Sn thin liquid layer. They found the cavitation effect could improve the wettability of the substrate metal surface, and the cavitation effect strengthened with decreasing gap layer.…”
Section: Introductionmentioning
confidence: 99%